New anti-seizure medication for elderly epilepsy patients - a critical narrative review. (24th March 2021) - Rohracher, A; Kalss, G.; Kuchukhidze, G.; Neuray, C.; Leitinger, M.; Höfler, J.; Kreidenhuber, R.; Rossini, F.; Volna, K.; Mauritz, M.; Poppert, N.; Lattanzi, S.; et al.
ABSTRACT: Introduction : The number of elderly patients with epilepsy is growing in resource rich countries due to demographic changes and increased longevity. Management in these patients is challenging as underlying etiology, co-morbidities, polypharmacy, age-related pharmacokinetic and pharmacodynamic changes need to be considered. Areas covered : Lacosamide, eslicarbazepine acetate, brivaracetam, and perampanel have been approved in the USA and Europe for monotherapy and/or adjunctive treatment of seizures in the last few years. The authors review the pharmacological properties and safety profile of these drugs and provide recommendations for their use in in the elderly. Expert opinion : There are only limited data available on more recent antiseizure medications (ASMs). Drugs with a low risk of interaction (lacosamide, brivaracetam) are preferred choices. Once daily formulations (perampanel and eslicarbazepine acetate) have the advantage of increased compliance. Intravenous formulations (brivaracetam and lacosamide) are useful in emergency situations and in patients who have difficulties to swallow. Dose adjustments are necessary for all ASMs used in the elderly with slow titration and lower target doses than in the regulatory trials. The adverse event profile does not significantly differ from that found in the general adult population.